Sharing economy model for the development of green economy - Liu Chong (2018)
In the context of "Internet +", a new shared economic model derived from practice has emerged and presented a rapid expansion trend. The essence of the sharing economy is to reduce transaction costs, divide and integrate excess idle resources, and then conduct transactions again on an open platform. In the consumption field, the sharing economy has subverted the original business model from the aspects of consumption concept, consumption mode and consumption range. In the field of the construction of ecological civilization, it promotes green consumption and advocates a green lifestyle. During the period of slowing economic growth, the sharing economy has brought rare opportunities to the world, which is conducive to the implementation of new development concepts, fostering new energy growth, promoting supply-side structural reforms, helping entrepreneurship and innovation, and building an information age. The sharing economy is accelerating the transformation of asset ownership, production organization, service supply, employment model and consumption pattern, representing the new development direction of the current and future period, and is becoming a new engine of economic growth.